Pośrednie. Co łączy Judith Butler i René Girarda? - Graczyk, Piotr (Civitas. Studia z filozofii polityki, 2017)
Starting from the performative vision of culture as a spectacle, which is based on a desire that is not determined by natural dispositions and creates unstable and social worlds lined with identity panic and threatened with mimetic rivalry leading to uncontrollable outbursts of violence, Judith Butler and René Girard come, despite their dif‌ferent sensitivities, to similar and sometimes complementary conclusions. While Butler somehow sympathises with collective acts of disobedience and Girard primarily fears massive outbursts of aggression, they both praise the intermediate. ‘The intermediate’ can be understood as social infrastructure (in a broad sense), which allows the establishment of individuality as a certain space for maneuver, an open f‌ield of interpretation within institutions guaranteeing its relative mental and physical security.